2019
DOI: 10.3758/s13423-019-01629-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral trainings and manipulations to reduce delay discounting: A systematic review

Abstract: In everyday decision-making, individuals make trade-offs between short-term and long-term benefits or costs. Depending on many factors, individuals may choose to wait for larger delayed reward, yet in other situations they may prefer the smaller, immediate reward. In addition to within-subject variation in the short-term versus long-term reward trade-off, there are also interindividual differences in delay discounting (DD), which have been shown to be quite stable. The extent to which individuals discount the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 208 publications
(310 reference statements)
4
69
0
6
Order By: Relevance
“…Interestingly, a recent review shows that individual rates of delay discounting can decrease through behavioral training, endorsing context-dependent and changeable attributes in impulsive choice behavior. The most promising avenues in this regard seem to be acceptance-/mindfulness-based trainings and manipulations involving future orientation (83). Thus, we cannot exclude that impulsive choice, which did not normalize after 3 months in our study, would have improved after a longer recovery time or after implementing the aforementioned treatment modules.…”
Section: Clinical Relevancementioning
confidence: 79%
“…Interestingly, a recent review shows that individual rates of delay discounting can decrease through behavioral training, endorsing context-dependent and changeable attributes in impulsive choice behavior. The most promising avenues in this regard seem to be acceptance-/mindfulness-based trainings and manipulations involving future orientation (83). Thus, we cannot exclude that impulsive choice, which did not normalize after 3 months in our study, would have improved after a longer recovery time or after implementing the aforementioned treatment modules.…”
Section: Clinical Relevancementioning
confidence: 79%
“…One of the tendencies that contribute to high impulsivity, fun seeking, and low inhibitory control of children is poor delayed gratification due to delay discounting [29]. As a result of poor delayed gratification, behaviors with immediate consequences are more likely to occur than behaviors with the delayed consequences [30,31]. Poor delayed gratification (high delay discounting) has implications for a wide range of outcomes such as obesity, sex, tobacco usage, alcohol usage, drug abuse, and gambling [29].…”
Section: Introductionmentioning
confidence: 99%
“…The participants in the concrete construal group were, too, more patient than the controls, with the observed effect size being even bigger (Cohen's d = 0.33 and 0.37 respectively). At a first glance, such pattern of the results seems to be counterintuitive and contrasting the existing literature, however, as noted by Scholten et al (2019) in their review covering almost a hundred studies aimed at decreasing delay discounting, both abstract and concrete mindsets seemed to be notably decreasing delay discounting rates. For instance, Kim et al (2013;study 1A, 1B and study 2) found that delay discounting was reduced when the hypothetical future option was construed more concretely and additional details were provided.…”
Section: Discussionmentioning
confidence: 74%